Pengaruh Good Corporate Governance Terhadap Kinerja Pengelolaan Koperasi Simpan Pinjam di Kabupaten Jembrana - Handayani, Putu Ari; Darmawan, Nyoman Ari Surya (Jurnal Akuntansi Profesi, 2024)
This research was conducted to find out the effect of Good Corporate Governance on the management performance of KSP in Jembrana Regency. This research uses a descriptive quantitative approach as a research method, with primary data sources obtained from distributing online questionnaires. The research population is KSP administrators who are still actively operating. Samples were taken using the purposive sampling method. The analysis technique used is multiple linear regression, and previously instrument testing and classical assumption testing were carried out for the accuracy of the regression analysis results. The research results provide evidence that the variables of accountability, responsibility, independence, and fairness have a positive and significant effect on the management performance of savings and loan cooperatives. Meanwhile, the transparency variable has a negative and significant effect on the management performance of savings and loan cooperatives.